2019
DOI: 10.1097/ccm.0000000000003557
|View full text |Cite
|
Sign up to set email alerts
|

Data Omission by Physician Trainees on ICU Rounds*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
(37 reference statements)
1
19
1
5
Order By: Relevance
“…36 In an assessment of medical student and resident intensive care unit (ICU) patient presentations, potentially important data were omitted from 157 of 157 presentations. 10 Even when data collection and analysis are complete, high decision-making volume begets decision fatigue, manifesting as procrastination, less persistence when facing adversity, decreased physical stamina, and lower quality and quantity of mathematic calculations. 49 These impairments are exacerbated by acute and chronic sleep deprivation, which occurs in as many as two-thirds of all acute care surgeons taking in-house call.…”
Section: Challenges In Surgical Decision-makingmentioning
confidence: 99%
“…36 In an assessment of medical student and resident intensive care unit (ICU) patient presentations, potentially important data were omitted from 157 of 157 presentations. 10 Even when data collection and analysis are complete, high decision-making volume begets decision fatigue, manifesting as procrastination, less persistence when facing adversity, decreased physical stamina, and lower quality and quantity of mathematic calculations. 49 These impairments are exacerbated by acute and chronic sleep deprivation, which occurs in as many as two-thirds of all acute care surgeons taking in-house call.…”
Section: Challenges In Surgical Decision-makingmentioning
confidence: 99%
“…1,2 Concomitantly, there is considerable evidence in the literature and even from personal anecdotal reports of which many are aware that suggest difficulties in using the EHR for patient care and research. For example, Artis et al found that incomplete data can lead to misdiagnosis and medical error when clinicians rely on the EHR when rounding 3 and during hand-offs. 4 These findings were substantiated in another study which found that physicians frequently identified poor EHR usability as a barrier to finding patient information.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to such a tracking document, one participant stated “If not for this, I would not be able to keep track of what I need to do over the course of the day.” While some problems might be hospital specific, interoperability/usability/integration issues across EHRs and the resulting spread of information and accompanying risks appear to be the norm rather than an exception, particularly in the United States. 6 7 22 24 25 46 47 48…”
Section: Discussionmentioning
confidence: 99%